Revitalizing the Walasuji Assilaibiningeng Tradition as a Foundation for Future Cultural Learning and Preservation in Barru Regency - M, A. Pananrangi; Supriadi, Supriadi (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The tradition of Walasuji Assilaibinengeng preserves traces of cosmological thought and social values within Bugis society. However, in the life of today’s generation, the meaning of this tradition has begun to erode due to the advancement of modern times. This study aims to explore the forms and symbolic meanings of walasuji and to examine the possibilities of its development through education. The research employed a qualitative descriptive method with an ethnographic approach, involving observation, interviews, and documentation in two villages in Barru Regency, South Sulawesi. The findings indicate that walasuji embodies values such as lempu’ (honesty), getteng (steadfastness), and siri’ (self-respect), which can be integrated into character education within the Merdeka Curriculum. A survey of teachers revealed that the majority support the internalization of walasuji in the Pancasila Student Profile Strengthening Project (P5). This study concludes that the preservation of local culture requires the active involvement of the educational sector, so that traditions are not only remembered but also sustained.